Family, Community and Long-Term Earnings Inequality - Paul Bingley; Lorenzo Cappellari; Konstantinos Tatsiramos (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
Correlations between the earnings of siblings reflect shared family and community background, but evidence is mixed on the relative magnitudes of these influences. We estimate long run earnings correlations between brothers, school mates and teenage neighbors jointly in a unified framework. Using administrative data on the Danish population we find that (1) family is by far the most relevant factor that shapes long-term earnings; (2) the contribution of neighborhood and school quality on long-term earnings is overestimated if the family component is ignored, and becomes negligible and not significantly different from zero by age 30; and (3) the importance of family declines over the life-cycle.
Keywords: D31; J62; 330; Sibling correlations; Neighborhoods; Schools; Life-cycle earnings; Inequality